Nutritional treatment in chronic kidney disease - review article - Maciej Orczykowski; Rafał Oleszczuk; Jakub Mendocha; Agnieszka Grzebalska (Kazimierz Wielki University, 2022)
INTRODUCTION: Chronic Kidney Disease (CKD) is a condition affecting nearly 16% of the population. It is a disease that cannot be completely cured with modern medical capabilities. However, it is possible to halt the progression of the disease and postpone renal replacement therapy through pharmacotherapy. In order to monitor the progression of the disease, GFR should be determined.        PURPOSE OF THE WORK: This article reviews the potential impact of typical Western diet and eating habits on the occurrence and progression of chronic kidney disease. Reducing the intake of animal protein, foods rich in sodium potassium and phosphorus, and increasing the intake of fruits, vegetables and fiber help prevent or delay end-stage renal disease. The literature on the role of a low-protein plant-based diet in patients with CKD was also reviewed.        DESCRIPTION OF THE STATE OF KNOWLEDGE: In addition to pharmacological methods, whose main goal is to reduce proteinuria and control blood pressure, drug therapy can be supported by non-pharmacological methods. One of them is the use of a low-protein diet and adequate provision of macro- and micronutrients in the diet.         SUMMARY: In order to support pharmacotherapy in the treatment of chronic kidney disease, the use of an appropriate diet plays an important role. According to the literature, the most important is restriction of protein supply, weight reduction in obese patients and supplementation of micronutrient deficiencies that occur.